2020
DOI: 10.1039/d0ta03957h
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid/base approach for efficacious defect passivation in perovskite solar cells

Abstract: The Lewis acid/base passivation strategy and its effects on energy level alignment, recombination kinetics, hysteresis behavior and operational stability for efficient perovskite solar cells are comprehensively reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
135
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 200 publications
5
135
0
1
Order By: Relevance
“…One of the promising approaches is to introduce passivation molecules as an additive into the perovskite materials in which those additive molecules act as electron acceptors or donors for the neutralization of the charged point defects. [ 24 ] Lewis acid molecules (such as phenyl‐C61‐butyric acid methyl ester (PC 60 BM)) accept electrons from negatively charged defects, [ 25 ] such as uncoordinated halide ions (e.g., I − ), [ 25,26 ] whereas Lewis base molecules (such as pyridine and thiophene) donate electrons to positively charged defects, such as uncoordinated lead ions (e.g., Pb 2+ ). [ 27–31 ] Although each of these cases demonstrates reasonable improvement in the performance of PeSCs, the application of Lewis acid or base molecules is capable of suppressing only the negatively or positively charged defects; thus the oppositely charged defects remain in the perovskite materials.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…One of the promising approaches is to introduce passivation molecules as an additive into the perovskite materials in which those additive molecules act as electron acceptors or donors for the neutralization of the charged point defects. [ 24 ] Lewis acid molecules (such as phenyl‐C61‐butyric acid methyl ester (PC 60 BM)) accept electrons from negatively charged defects, [ 25 ] such as uncoordinated halide ions (e.g., I − ), [ 25,26 ] whereas Lewis base molecules (such as pyridine and thiophene) donate electrons to positively charged defects, such as uncoordinated lead ions (e.g., Pb 2+ ). [ 27–31 ] Although each of these cases demonstrates reasonable improvement in the performance of PeSCs, the application of Lewis acid or base molecules is capable of suppressing only the negatively or positively charged defects; thus the oppositely charged defects remain in the perovskite materials.…”
Section: Figurementioning
confidence: 99%
“…uncoordinated halide ions (e.g., I − ), [25,26] whereas Lewis base molecules (such as pyridine and thiophene) donate electrons to positively charged defects, such as uncoordinated lead ions (e.g., Pb 2+ ). [27][28][29][30][31] Although each of these cases demonstrates reasonable improvement in the performance of PeSCs, the application of Lewis acid or base molecules is capable of suppressing only the negatively or positively charged defects; thus the oppositely charged defects remain in the perovskite materials.…”
mentioning
confidence: 99%
“…Organic-inorganic lead halide perovskite solar cells (PSCs) have attracted extensive attention due to their high optical absorption coefficient, high carrier mobility, low exciton binding energy, films. [14][15][16][17] Therefore, the fabrication of high-quality perovskite films with large grain size, small GB density, and low defect density is critical to achieving efficient and stable PSCs. In the past, various strategies have been developed to improve the perovskite film quality, such as perovskite composition modulation, [18] precursor solvent, and antisolvent engineering, [19] deposition substrate modulation, [20] additive engineering, [21] etc.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Till now, additive engineering, solvent engineering, component engineering, interface engineering, and dimension engineering have been developed to passivate the point defects, surface, and GBs defects. [27][28][29][30][31][32][33] For these reasons, many reviews on the defects of PSCs have been reported, however, most of them focus on summarizing different passivation methods, and do not specifically dissect complex defects; [34][35][36][37][38][39][40] also some reviews described the related mechanisms of defects restrainedly; [41][42][43][44][45][46] Although there are some reviews that satisfactorily explain the effect of defects on the performance of solar cells, the descriptions of the formation of defects are conservative. [47][48][49][50][51] Therefore, it is urgent to conduct an in-depth and systematic comparative analysis of the formation and impact of various defects, and then choose the appropriate passivation method reasonably.…”
Section: Introductionmentioning
confidence: 99%